EFFECT OF SPRAYING IRON AND ZINC ON SOME VEGETATIVE PROPERTIES AND YIELD OF WHEAT BUHOOTH -7 - AL-Salmani , Hameed K.; ALTimimi , Mohmmed S.; AL-Bandawy , Bassim R. (Diyala Agricultural Sciences Journal, 2013)
To study the effect of spraying ferrous and zinc sulfates on some of vegetative properties and yield of grain of wheat buhooth -7 .Factorial experiment was conducted at Field of crop production sciences . College of Agriculture – university of Baghdad . Requirements of N, P and K Fertilizers were added ,three concentrations of Fe (0,50.100 ) mg.L-1 and three concentrations of Zn (0,50.100 ) mg.L-1 were sprayed at three stages of wheat growth ( vegetative growth , boating and Flowering stages of crop growth ) . Randomized complete block design was used at three replicated . Results showed that : All concentrations of Fe , Zn and their interactions were significantly affected on all plant parameters under study . High values were produced of interactions of Fe 2 × Zn 2 which were : 122.5 cm , 43.2 cm 2 , 9 filler per plant , 50.2 spad unit and 5.88 t.ha-1 for plant height , flag leaf area , tiller per plant , chlorophyll index and yield of grains respectively .